2014
DOI: 10.1007/s13233-014-2137-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-polishing behavior of zinc-based copolymer with different monomer composition

Abstract: The zinc methacrylate copolymers with various monomer compositions were prepared for investigating the effect of zinc methacrylate (ZMA), 2-methoxyethyl acrylate (2-MTA) contents and compositions of ethyl acrylate (EA) and methyl methacrylate (MMA) as hydrophobic monomers on self-polishing behavior. The effect of molecular weight of the self-polishing copolymer (SPC) was also investigated. The characterizations of copolymers were performed by Fourier transform infrared spectroscopy (FTIR), 1 H nuclear magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…For example, acrylate esters are still used in SPCs because they act as antifouling agents, while hydrolysable pendant groups, such as TBT, have been substituted with environmentally safe components. In particular, zinc methacrylate (ZMA) [12][13][14], copper methacrylate (CMA) [2,15], and triisopropylsilyl acrylate (TIPSA) [8,14] have been investigated as hydrolysable pendant antifouling agents [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, acrylate esters are still used in SPCs because they act as antifouling agents, while hydrolysable pendant groups, such as TBT, have been substituted with environmentally safe components. In particular, zinc methacrylate (ZMA) [12][13][14], copper methacrylate (CMA) [2,15], and triisopropylsilyl acrylate (TIPSA) [8,14] have been investigated as hydrolysable pendant antifouling agents [1].…”
Section: Introductionmentioning
confidence: 99%
“…The polishing and leaching behaviour of an SPC is affected by the type and content of the SPC pendant group. Kim et al [12] reported that the ZMA content in an SPC is important to its self-polishing behaviour, with increasing SPC leaching observed with increasing ZMA content. In particular, the leaching rate affects the erosion rate, as the SPC erosion rate is closely related to the leaching behaviour of the SPC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few researchers have reported the good antifouling performance of PU coatings in both SPC coatings and fouling-resistant coatings [1,17,18,19]. Similar to other SPC coatings, the PU-based SPC coating performance depends on hydrolytic degradation, which depends on the PU molecular weight and its structure, as well as the hydrolysable pendant group.…”
Section: Introductionmentioning
confidence: 99%